Densification Behavior, Microstructure, and Property of ZnO with Multi-Oxides Glass Addition at Different Sintering Temperatures - Houng, Boen; Wei-Chueh Chien; Chen-Kai Sun (Proceedings of Engineering and Technology Innovation, 2020)
Zinc Oxide (ZnO) mixed with various amount of glasses were sintered at different temperatures. The densification behavior of zinc oxide with glass addition and its microstructure and dielectric constant sintered from 900° to 1200°C have been investigated. A unique glass composition contained GeO2, MoO3, and V2O5 (GMV) was designed to act as the sintering aid to enhance the densification and to adjust the dielectric constant of ZnO. The effect of sintering temperature on the densification behavior and dielectrics properties of ZnO was investigated by dilatometer, x-ray diffractometer, scanning electron microscopy and LCR meter. The glass additive formed a thin continuous liquid phase and rearranged ZnO particles into a dense microstructure at relatively low temperature. The dielectric constants of glass added ZnO ceramics were found to vary with the glass concentration and sintering temperature.